Evaluation of the Prospects for the Use of Microalgae in Functional Bread Production - Stanislav Sukhikh; Svetlana Ivanova; Vyacheslav Dolganyuk; Inna Pilevinova; Alexander Prosekov; Elena Ulrikh; Svetlana Noskova; Philippe Michaud; Olga Babich (Applied Sciences, 2022)
Microalgae are widely used to produce sorbitol, ethyl and methyl alcohols, acetone, organic acids, esters, pigments, chlorophylls, carotenoids, and other compounds. The purpose of this work was to study the potential of the Baltic Sea microalgae Arthrospira platensis and Chlorella vulgaris, as new ingredients for functional bread. Bread was baked with a dry mixture of Arthrospira platensis and Chlorella vulgaris microalgae (1:1). Gas chromatography, sequencing, chromametry, pH-metry, rheological methods, methods for determining the antioxidant ability of bread samples with microalgae for ferric reduction and removal of active free radicals were used for the research. When baking bread, the organoleptic, physicochemical properties, density, coefficients of elasticity, chewiness, stickiness, resistance to crumbling, the content of polyphenols and volatile compounds in the samples of bread with microalgae were controlled. It was found that with a higher content of microalgae in bread (3% of the flour weight on dry basis), the color of the crust and crumb decreased due to the degradation of the pigment during baking. The specific volume of a loaf with a large amount of microalgae (5%) was lower than the volume of loaves with the addition of 1% and 3% microalgae. It is shown that the moisture content increased with an increase in the amount of microalgae in bread. Replacing wheat flour with the amounts of microalgae of 1% and 3% did not affect the pH and water activity in bread. With the addition of 5% microalgae, bread became more sour, sticky, with a slight “fishy” smell. The addition of more microalgae led to an increase in polyphenols in bread samples, and, accordingly, to an increased antioxidant capacity. In total, 42 volatile compounds were found in bread with microalgae, which makes it possible to obtain functional bread. It is assumed that in the future, bread with microalgae will be competitive with ordinary wheat bread due to improved nutritional and biological value.